Perceptions of Self-concept and Self-presentation by Procrastinators: Further Evidence - Ferrari, Joseph R.; Díaz Morales, Juan Francisco (The Spanish Journal of Psychology, 2007)
Two samples of university students completed self-report measures of chronic procrastination and either self-concept variables (Sample 1, n = 233) or self-presentational styles (Sample 2, n = 210). Results indicated that procrastination was significantly related to a self-concept of oneself as dominated by issues related to task performance, and to self presentation strategies that reflected a person as continually justifying and excusing task delays and being “needy” of others’ approval. It seems that men and women procrastinate in order to improve their social standing by making their accomplishments seem greater than they really are.
Keywords: Procrastination; Self-concept; Self-presentation